বিশাল বাংলায় - হক, সৈয়দ শামসুল. (ঢাকা: মাওলা ব্রাদার্স, 2006)
Autobiography of a 20th century Bengali author from Bangladesh.
In Bengali.
Keywords: Huq, Syed Shamsul; Authors, Bengali -- Bangladesh -- Biography; Authors, Bengali -- 20th century -- Biography